Factors Affecting Critical Features of Fundamental Movement Skills in Young Children - Miha Marinsek; Iva Blazevic; Silvester Liposek (Montenegrin Sports Academy, 2019)
Despite significant advances in the knowledge and understanding of associations between the phenomenon of excess body weight (hereafter "overweightness") and fundamental movement skill (FMS) proficiency, the question of how overweightness affects critical features of movement remains unanswered. This study examined the differences in the proficiency of FMS between boys and girls with different weight status on the level of critical features. Three hundred and twenty-two boys and girls aged 5 to 10 years were assessed in eight FMS (run, vertical jump, long jump, ball catch, ball kick, ball pass, ball bounce, and forehand strike) and were assigned to non-overweight and overweight groups according to their waist-to-height ratio, with a cut-off point of 0.5. FMS score differences (p < 0.05) between boys and girls that can be frequently observed in the non-overweight group of children were not determined in the overweight group of children (p ≥ 0.131). Overweight boys performed worse in a higher number of skills' critical features than overweight girls did when compared to non-overweight groups. With weight gain, boys might experience a more significant decline in FMS proficiency than girls do because of the higher scores when non-overweight. The critical features of FMS indicate that overweightness might affect postural control and coordination, which this paper discusses.